1968
DOI: 10.1111/j.1365-3180.1968.tb01400.x
|View full text |Cite
|
Sign up to set email alerts
|

Rate of Detoxification of 4‐amino‐3,5,6‐trichloropicolinic Acid in Soil

Abstract: 4-Aniino-3,5,6-trichloropicolinic acid was incubated at 70° F in thirteen different soils for periods of up to 2 years at a concentration range of 0-023-24 ppm. Losses varied from complete to non-mrasurable by the bioassay technique employed. The percentage decomposed was generally greater for lower initial concentrations. The results were mathematically analysed in terms of zero-order, half-order, first-order and Michaclis-Menten kinetics. Half-order and Mirhaelis-Menten were found to hv the kinetic expressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

1970
1970
1991
1991

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(15 citation statements)
references
References 5 publications
1
14
0
Order By: Relevance
“…However, Youngson et al (1967) also studied the degradation of picloram and confirmed first-order kinetics, but did not find a lag phase. In a later paper by the same group (Hamaker, Youngson & Goring, 1968) it was found that half-order and Michaelis-Mentcn kinetics most satisfactorily described the degradation of picloram in soil.…”
Section: Introductionmentioning
confidence: 96%
“…However, Youngson et al (1967) also studied the degradation of picloram and confirmed first-order kinetics, but did not find a lag phase. In a later paper by the same group (Hamaker, Youngson & Goring, 1968) it was found that half-order and Michaelis-Mentcn kinetics most satisfactorily described the degradation of picloram in soil.…”
Section: Introductionmentioning
confidence: 96%
“…However, Hamaker el a1. 3 showed that picloram degradation was better described by a hyperbolic expression. Hance and M~K o n e ,~ found that the decomposition of atrazine, linuron and picloram could not be described very well by the first-order rate law, nor by zero, half or Michaelis-Menten kinetics.…”
Section: Introductionmentioning
confidence: 99%
“…A great deal of effort has gone into the preparation of kinetic curves for degradation of pesticides presently in use. Imperical data are generally fitted to some sort of decay curve, such as the power rate model (Hamaker 1972), the Monod model (Monod 1949), the logistic curve (Odum 1971), Michaelis Menten kinetics (Alexander and Scow 1989;Hance and McKone 1971;Hamaker et al 1968;Somas 1982), and multiple compartment models (Alexander and Scow 1989;Hamaker and Goring 1976).…”
Section: Predicting Environmental Fate Of Pesticidesmentioning
confidence: 99%